ANALISIS NUTRISI DAN ASAM AMINO TEPUNG MAGGOT - Dewi Putri Lestari; Salnida Yuniarti Lumbessy; Dewi Nur'aeni Setyowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Maggot meal is known as a raw material for making feed which can be used in various fisheries and livestock industries. Study of the use of maggot meal as a feed ingredient because it has high nutritional content.This results of maggot meal have nutritional content in dry weight such as Protein content values ranging from (33.15-48.36%), fat (19.35-41.92), Ash (0.63-9.19), Crude Fiber (5.98-7.57%) and BETN (15.51-18.30%). The content of Amino Acids obtained from the test results is the content of essential amino acids and the content of non-essential amino acids. The content of essential amino acids ranges from 29.53-30.96% and the content of non-essential amino acids ranges from 64.44-65.53%.